Analysis of Soybean Embryonic Axis Proteins by Two-Dimensional Gel Electrophoresis and Mass Spectrometry - Savithiry S. Natarajan; Hari B. Krishnan; Farooq Khan; Xi Chen; Wesley M. Garrett; Dilip Lakshman (Journal of Basic & Applied Sciences, 2021)
A proteomic approach based on two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) for protein separation and subsequent mass spectrometry (MS) for protein identification was applied to establish a proteomic reference map for the soybean embryonic axis. Proteins were extracted from dissected embryonic axes and separated in the first dimension using a pH range from 4-7. A total of 401 protein spots were isolated, digested with trypsin, and analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). We identified 335 protein spots by searching National Center for Biotechnology Information (NCBI) non redundant databases using the Mascot search engine and found a total of 200 unique proteins. Gene Ontology (GO) analysis was employed to understand the molecular processes in which the identified embryonic axes proteins are involved. The majority of proteins play a functional role in catalytic activity (42.9%) and binding (39.3%), followed by nutrient reservoir activity (5.3%), structural molecular activity (4.0%), antioxidant activity (3.2%), transporter activity (2.4%), enzyme regulator activity (1.2%), molecular transducer activity (0.8%), and transcription regulator activity (0.8%). Our 2D-profiling of soybean axis proteins has established for the first time a baseline proteome on which to investigate and compare factors affecting soybean embryonic development and the interaction of beneficial and pathogenic soilborne organisms during seed germination.